Enhancing the tumoricidal efficacy of the nanobubbles-mediated PD-L1 inhibition and immunogenic cell death in mice - Liu, Yun; Han, Jiaxuan; Liu, Chaoqi; Chen, Yezi; Yang, Shiqi; Ma, Yao; Zhou, Chang; Liu, Rong; Hu, Yu; Zhao, Yun (Frontiers in Immunology, 2026)
BackgroundImmunotherapy becoming the focus of contemporary multidisciplinary collaborative research efforts towards advanced hepatocellular carcinoma (HCC).ObjectiveThis study aims to develop a nanobubble (NB) delivery system designed to co-administer an immunogenic cell death (ICD) inducer, Shikonin (SK), alongside an immune checkpoint inhibitor, miR-497-5p, to enhance the efficacy of the immune response against liver cancer.MethodsNBs were synthesized through thin-film hydration and mechanical oscillation techniques to encapsulate miR-497 and SK. Comprehensive characterization and pharmacokinetic analyses of the miR-497/SK-loaded NBs were conducted both in vitro and in vivo. To evaluate the anti-tumor efficacy and immunological activity of this combination therapy, a subcutaneous transplanted tumor model using H22 hepatoma cells was established.ResultsThe miR-497/SK-NBs demonstrated an optimal morphology and size, as well as excellent gene capacity and SK encapsulation. The in vivo anti-tumor effects and mechanisms of SK and miR-497 were assessed in H22 hepatoma transplants model. The miR-497/SK-NBs group showed the strongest tumor inhibition, with their synergistic immunotherapeutic effect demonstrated through two main mechanisms. Initially, the activation of SK, facilitated by ultrasound, triggered the induction of injury-related molecular patterns, including CRT and HMGB1. This process subsequently activated CD80+ CD86+ macrophages, thereby enhancing the presentation of tumor antigens. Subsequently, miR-497 contributed to the downregulation of PD-L1 expression in tumor cells. Collectively, these processes elicited a robust systemic anti-tumor immune response and induced apoptosis in tumor cells within murine HCC models.ConclusionsThe study demonstrated that miR-497/SK-loaded nanobubbles simultaneously boosts ICD and blocks the PD-1/PD-L1 pathway in immunotherapy. This finding offers a theoretical foundation for the effective eradication of tumor cells and the development of a highly efficient synergistic treatment strategy for HCC.